ANALISIS KENAIKAN PAJAK PERTAMBAHAN NILAI DI PERUSAHAAN CV. CAHAYA PRIMA MANDIRI DALAM PERSPEKTIF EKONOMI ISLAM - Masyhari; Agus Khaerudin (Al Naqdu, 2021)
The taxation sector is one of the “sources of state financial cash receipts” by taking part of a person’s income as well as levies on the purchase of an item. Article 7 of Law Number 7 of 2021 the government issued a policy in an effort to increase the state revenue treasury by increasing the Value Added Tax to 11%, which was to be precise in early April. The policy is not too burdensome for a company, but in the midst of the Covid-19 pandemic that still exists and the company’s economy has not yet recovered, it is an obstacle for companies to recove their economy. There were several companies that experienced the impact of the VAT increase itself at the beginning of the policy, because the company had to replace all systems that previously used 10% VAT to 11%. This change would take a long time